2012
DOI: 10.2478/s11532-012-0181-4
|View full text |Cite
|
Sign up to set email alerts
|

First synthesis of important secondary oxidative metabolites of morphine and codeine with the Michael addition

Abstract: Morphine (1) and codeine (2) are two representatives of medically important, frequently used natural opiates, therefore the exploration of their metabolic pathways and the exact characterization of the metabolites are main targets of their pharmacological studies. These morphinans also play a crucial role in drug abuse; therefore, the analysis and preparation of the metabolites for identification and quantitation in human samples are considered important aims. In order to allow the in-depth analysis of metabol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 21 publications
0
4
1
Order By: Relevance
“…[27] However, the NMR data and optical rotation reported differed considerably from that obtained for compound 21 prepared in methanol solution as described in this work. Employing the previously reported experimental procedure [27] provided a sample with identical 1 H NMR and optical rotation to that prepared in methanol. A comparison of the 1 H and 13 C NMR data for the two reports is given in the Supplementary Material together with copies of 1D and 2D NMR spectra.…”
Section: Reaction Kineticscontrasting
confidence: 82%
See 1 more Smart Citation
“…[27] However, the NMR data and optical rotation reported differed considerably from that obtained for compound 21 prepared in methanol solution as described in this work. Employing the previously reported experimental procedure [27] provided a sample with identical 1 H NMR and optical rotation to that prepared in methanol. A comparison of the 1 H and 13 C NMR data for the two reports is given in the Supplementary Material together with copies of 1D and 2D NMR spectra.…”
Section: Reaction Kineticscontrasting
confidence: 82%
“…½a 20 D þ22 (c 1.0 in CHCl 3 ) (lit½a 20 D À127 (c 0.5 in CHCl 3 ) [27] 8,170.9,169.9,145.2,143.1,126.8,126.5,120.4,115.0,91.5,57.0,56.9,52.6,52.3,47.5,47.4,47.3,47.2,43.0,41.6,35.7,31.5,23.2,19.3. m/z (EI) The literature procedure [27] was applied to codeinone (5, 20 mg, 67 mmol) using N-acetyl-L-cysteine methyl ester …”
Section: Codeinone-n-acetyl-l-cysteine Methyl Ester Adductmentioning
confidence: 99%
“…Morphinone, a reactive electrophile, is another major product of opioid metabolism in the liver [ 25 , 26 ]. Morphinone binds covalently to proteins in liver specifically at cysteines to produce morphinone–cysteine adducts that interfere with protein function [ 27 , 28 , 29 , 30 ]. This adduct reaction is inhibited, and protein function maintained, by the presence of sulfhydryl compounds such as glutathione and L-cysteine [ 28 , 31 ], S -adenosyl- l -methionine [ 32 ], and the disulfide-containing garlic compound ajoene (( E )-1-(prop-2-enyldisulfanyl)-3-prop-2-enylsulfinylprop-1-ene) [ 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…Codeine, which is naturally metabolized to morphine, can similarly be metabolized into morphinone but also into codeinone [ 38 , 39 ]. Codeinone, which can form adducts with glutathione [ 29 , 40 ], is toxic at high concentrations [ 41 , 42 ] and is, like morphinone, antagonized by the co-administration of either glutathione or L-cysteine by forming neutralizing adducts [ 38 ].…”
Section: Introductionmentioning
confidence: 99%
“…bohemicum R89-1 grown in an LB medium (a reference sample) was compared to that grown in an LB medium supplemented by codeine, a XdpB substrate, and a precursor of codeinone. Codeinone is a highly reactive α, β-unsaturated keton, a compound disrupting the cell redox state by Michael addition [ 58 ], and inducing oxidative stress. Our previous data indicated that codeinone, 14-OH-codeinone, and products of XdpB mediated conversion hydrocodone and oxycodone were present in A .…”
Section: Resultsmentioning
confidence: 99%